Monopoly sale of a network good - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper studies the problem of a monopolist who sells a network good through a price posting scheme. The scheme posts a price of every possible allocation for each buyer, who are then asked to report their private information to the seller. The seller then implements the allocation based on the reports. The social choice functions that are ex post implementable through such a sales scheme are characterized, and the conditions are identified under which the revenue maximizing scheme has the property that the price of a larger network is more affordable than that of a smaller network.
Keywords: C72; D82; 330; network externalities; ex post equilibrium; revenue maximization; Netzwerkökonomik; Monopol; Asymmetrische Information; Eigeninteresse; Soziale Wohlfahrtsfunktion; Nichtkooperatives Spiel; Theorie